Case report: recurrent epistaxis as a consequence of massive inverted papilloma of the sinonasal region - Tadić, Teodora (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction The inverted papilloma is the most common benign tumor of sinonasal region, which has a locally destructive growth pattern, tendency to recur, and can become malignant. It grows from the epithelium of the sinonasal mucosa. One of the clinical signs is epistaxis, which represents an emergency case. The aim of this case report is to illustrate basic characteristics of inverted papillomas, which in some patients could be a cause of recurrent epistaxis. Case report A female patient aged 75 came to our ear, nose, and throat emergency room because of repetitive left-sided nose bleeds. Clinically, histopathologically, and by radiological scans, we confirmed the diagnosis of inverted papilloma. Soon after, the patient was operated on. Conclusion In patients with recurrent nose bleeds, an accurate diagnosis of inverted papilloma is needed for planning the future surgical treatment in order to avoid recurrence, local destruction and malignant alteration of inverted papilloma.